PADRONIZAÇÃO DE OPERAÇÕES: UMA APLICAÇÃO NO SERVIÇO DE EXECUÇÃO DE FÔRMAS - Silveira, Amanda; Laval, Luiz Gustavo; Stanisci, Rodrigo; Zanotto, Gustavo; Lantelme, Elvira M. V.; Costella, Marcelo (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Standard Operating Procedures are a set tools developed within the Toyota Production System for continuous improvement and standardization or work. This article sought to evaluate the results of a simplified application of this tool in the assembly service of concrete forms in order to measure the time spent on value-adding and non-value-adding activities. The results obtained from the study indicated 80% reductions in the accumulated time per team in the same activity, and up to 59% in the total cycle time of the service. These gains were obtained from the definition of a standard operation that include redefining teams, eliminating non value-adding activities, reducing and / or eliminating rework and waiting times, improving the understanding of each task needed to complete the activity and the constant improvement of the techniques and processes involved.